METAFONT를 이용한 구조적 한글 폰트 생성기 - 권경재(Gyeongjae Gwon); 손민주(Minju Son); 최재영(Jaeyoung Choi); 정근호(Geunho Jeong) (정보과학회 컴퓨팅의 실제 논문지, 2016)
한글의 자소들은 몇 가지의 획으로 구성되어 있고, 완전한 글자들은 자소들의 조합으로 구성되어 있다. 획과 자소들을 조합하는 과정에서 그 구성들의 크기나 위치가 변화할 수 있으므로 폰트를 제작하는데 많은 노력이 필요하다. 이와 달리 METAFONT는 매개변수 값을 변경하면서 획과 자소의 크기와 위치를 쉽게 변환할 수 있는 시스템을 제공하여 폰트 제작 과정에 효율성을 높일 수 있다. 본 논문은 METAFONT를 기반으로 사용자가 매개변수를 수정하여 다양한 폰트를 자동으로 생성할 수 있는 구조적 한글 폰트 생성기를 제안한다. 본 논문에서 제안한 한글 폰트 생성기는 폰트 임베딩 분야와 폰트 편집기 분야에 적용할 수 있다. Radicals of Korean characters consist of some strokes, and complete letters are comprised of a combination of radicals. During the process of combining strokes and radicals, it requires a lot of effort as the size and the position of the components can be changed. Unlike this, METAFONT can improve the efficiency in the production process of fonts by changing its parameters. It also provides a system which can easily transform size and position of the strokes and radicals. We propose a structural Korean font generator which allows users to modify parameters of letters through METAFONT and generates a variety of fonts automatically. The suggested Korean font generator can be applied to font embedding and font editor. KCI Citation Count: 2